How to draw manga monsters - Eason, Sarah (BearPort Publishing, 2025)
"Manga monsters can be spooky and scary or cutely creepy. Learn to draw five manga monsters, including a cute ghost, a growling werewolf, and a cursed mummy. Alongside the step-by-step instructions for mastering each manga monster, helpful hints teach aspiring artists techniques of the trade and fun facts help readers learn more about the creatures they are creating"--
Manga everywhere! -- Spooked ghost -- Cursed mummy -- Growling werewolf -- Screaming banshee -- Cute monster.
Includes bibliographical references and index.
Ages 7-8
Grades 2-3
Keywords: Manga (Comic books) -- Juvenile literature; Cartooning -- Technique -- Juvenile literature; Monsters in art -- Juvenile literature